Analisis Beban Kerja Operator Mesin Cnc Laser Salvagnini Dengan Metode Fte Di PT. Xyz - Muhammad Ilham Romadoni; Rr. Rochmoeljati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
XYZ is one of the largest manufacturers of bus houses in Indonesia as a safe and reliable means of transportation with almost 50 years of experience. In carrying out the production process, employees are required to always be optimal in completing their work, but on the other hand, employees have limited workloads. The aim of this research is to determine the workload conditions received by Salvagnini CNC Laser machine operators, as well as to provide suggestions for improvements to the preparation department (Salvagnini). In order to find out the workload conditions for operators from this department, workload calculations are carried out using the FTE (Full Time Equivalent) method which is obtained from observing job descriptions, units of output or types of activities produced by operators (units/activities), vol-umes containing the number of production results. , as well as the duration of work carried out by the operator. The operator's workload conditions on the first and third days were FTE values of 0.671 and 0.949 (underload) because the FTE value was <0.99, while on the second day the workload condition was 1.033 (fit) because the FTE value was between 1-1.28.